B-cell clonality in the liver of hepatitis C virus-infected patients - Fan, He-Bin (The WJG Press and Baishideng, 2009)
AIM: The association of hepatitis C virus (HCV) infection with type II mixed cryoglobulinemia is well established, but the role of HCV in B-cell lymphoma remains controversial. In patients with HCV infection, B-cell clonal expansions have been detected in peripheral blood and bone marrow, and a high prevalence of B-cell non-Hodgkin’s lymphomas has been documented. Liver biopsies in chronic HCV infection frequently show portal lymphoid infiltrates with features of B follicles, whose clonality has not yet been investigated. The object of this study was to determine the frequency of liver-infiltrating monoclonal B-cells in 40 patients with HCV infection. METHODS: Eight hundred and forty-eight patients were studied prospectively, including 40 HCV-positive patients and 808 patients with chronic hepatitis B virus (HBV) infection. Immunohistochemical study for B- and T-cell markers was performed on the paraffin-embedded liver tissue sections. The clonality of lymphoid B-cells was tested using a polymerase chain reaction (PCR) approach designed to identify immunoglobulin heavy chain gene (IgH) rearrangements. RESULTS: Liver-infiltrating monoclonal B-cells were detected in the liver for 4 (10%) of 40 HCV-positive patients but were present in only 3 (0.37%) of 808 liver biopsy specimens with chronic HBV infection. Chi-square testing showed that the monoclonal B-cells infiltration in the liver was more frequent in the HCV-infected patients (P = 0.000). A clonal IgH rearrangement was detected in 5 (71.4%) of 7 liver biopsy specimens with monoclonal B-cells infiltration. In 2 of 5 patients with both a clonal B-cell expansion and monoclonal B-cells infiltration in the liver, a definite B-cell malignancy was finally diagnosed. CONCLUSION: Liver-infiltrating monoclonal B-cells are detected in the liver of patients with chronic HCV and HBV infection. A high percentage of patients with monoclonal B-cells infiltration and B-cell clonality in the liver were finally diagnosed as having a definite B-cell malignancy.